2018
DOI: 10.1039/c7sc04649a
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective17O enrichment and NMR spectroscopy of mixed-metal terephthalate metal–organic frameworks

Abstract: Cost-effective 17O enrichment of metal–organic frameworks enables the composition and disorder in mixed-metal materials to be determined using NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(185 citation statements)
references
References 63 publications
13
172
0
Order By: Relevance
“…In contrast, the V IV =O EPR spectra for the np-h and as states reveal that at least two distinct dopant sites exist, as indicated by arrows in Figure 1. Similar conclusions on inequivalence of the metal sites in these two states were obtained from magic angle spinning nuclear magnetic resonance studies [15,16]. Finally, exposure of the MOF to O2 (paramagnetic), either pure or in air, led to a marked EPR linewidth increase for frameworks in the lp state, but had virtually no effect for the three other states.…”
Section: Introductionsupporting
confidence: 73%
“…In contrast, the V IV =O EPR spectra for the np-h and as states reveal that at least two distinct dopant sites exist, as indicated by arrows in Figure 1. Similar conclusions on inequivalence of the metal sites in these two states were obtained from magic angle spinning nuclear magnetic resonance studies [15,16]. Finally, exposure of the MOF to O2 (paramagnetic), either pure or in air, led to a marked EPR linewidth increase for frameworks in the lp state, but had virtually no effect for the three other states.…”
Section: Introductionsupporting
confidence: 73%
“…17 O required in a synthesis or reaction, such as dry gel conversion methods, ionothermal reactions, or the use of very low reaction volumes, have been employed to reduce the cost of producing enriched material. [78][79][80][81] In addition to the improvement in sensitivity, enrichment has further advantages, including the possibility to utilize other interactions (such as the 2 H quadrupolar interaction to study dynamics, as discussed above) or the use of selective enrichment to aid spectral assignment 82,83 or simplify complex spectra of biomolecules. 83 It is also possible to improve the efficiency of many NMR experiments by careful choice/optimisation of the RF pulse sequence used.…”
Section: Sensitivity Enhancementmentioning
confidence: 99%
“…[70a] By using 17 OM AS-NMR spectroscopy,B ignami et al were able to determine the distribution of Al and Ga in mixed-metal MIL-53 materials. [90] They analyzedt he signals originating from the metal bridging hydroxyl groups and found that only as mall proportion of the hydroxyl groups bridged an Al/Ga pair,w hile most of the hydroxyl groups bridged Al/Al or Ga/Ga pairs.…”
Section: Characterization Of Mixed-metal Mofsmentioning
confidence: 99%